The Influence of Smartphone Technology Innovation On Mobile Product Sales at Atlantic Cell Stores in Bandung - Siti Komariah Hildayanti; Tuti Sulastri; Seflidiana Roza; Siska Yulia Defitri (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Recent technological advancements in smartphones, including 5G connectivity, AI-enhanced cameras, foldable screens, and improved biometric security, have notably transformed the telecommunications sector.Purpose: This research examines the impact of these innovations on the sales growth of mobile phone products at Atlantic Cell stores in Bandung.Design/methodology/approach: Using quantitative analysis, we collected sales data before and after the launch of the latest smartphone models, applying statistical techniques such as regression analysis and paired t-tests.Findings/Result: Our results show that sales of 5G-enabled smartphones increased by 12%, foldable phones by 7%, and AI-powered cameras contributed to a 9% growth. This indicates a strong relationship between technological innovations and shifts in consumer purchasing behavior.Conclusion: The findings highlight the importance for industry stakeholders, particularly retailers like Atlantic Cell, to stay aligned with emerging technological trends to remain competitive. By offering products that incorporate the latest innovations, businesses can enhance sales growth and ensure long-term success in a rapidly changing market.Originality/value (State of the art): This study emphasizes the necessity of continuously adapting to technological advancements to thrive in the competitive landscape of mobile phones. Keywords: atlantic cell, mobile product sales, shopping preferences, smartphones, technology updates, telecommunications industry